2011
DOI: 10.1603/an10147
|View full text |Cite
|
Sign up to set email alerts
|

Response ofBemisia tabaci(Hemiptera: Aleyrodidae) to Vapor Pressure Deficit: Oviposition, Immature Survival, and Body Size

Abstract: Whiteflies cause major agricultural problems in environments ranging from arid to humid climates on a global scale. A study was conducted on the effects of vapor pressure deficit ( VPD) on oviposition, hatching, body size, and survival of immature B-biotype sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). Experiments were conducted at VPD conditions of 0.5, 1.7, and 2.7 kPa to represent low, medium, and high VPD environments, respectively. The study was conducted at 26°C with insects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This spatial correlation analysis shows clear indications of drought conditions under July air temperature increase. A few studies 37 , 38 showed a drastic VPD increase and a relative humidity decrease after the 2000s for other sites worldwide.
Figure 3 Spatial correlation maps of VPD reconstructed data versus gridded maximum July temperature (a) and July evapotranspiration (b) for the available period 1979–2004, respectively.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This spatial correlation analysis shows clear indications of drought conditions under July air temperature increase. A few studies 37 , 38 showed a drastic VPD increase and a relative humidity decrease after the 2000s for other sites worldwide.
Figure 3 Spatial correlation maps of VPD reconstructed data versus gridded maximum July temperature (a) and July evapotranspiration (b) for the available period 1979–2004, respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…This spatial correlation analysis shows clear indications of drought conditions under July air temperature increase. A few studies 37,38 showed a drastic VPD increase and a relative humidity decrease after the 2000s for other sites worldwide.…”
Section: Spatio-temporal Patterns Of Evapotranspiration Variability Omentioning
confidence: 99%
“…He mentioned that effective control of B. tabaci was achieved by releases of an unidentifi ed species of Lasioseius in screenhouses, with reductions of about 80 % of the pest population after 20 days of predator release. The use of mites of the ascid complex seems promising for the control of this pest, given that B. tabaci is favored by high level of relative humidity (Simmons and Mahroof 2011 ), which is also favorable to mites of the ascid complex.…”
Section: Other Insectsmentioning
confidence: 99%
“…Greenhouses commonly have elevated moisture levels compared with open environments. Moderately high ambient moisture can be more beneÞcial for the populations of both D. catalinae (Simmons et al 2008b) and its whiteßy prey (Simmons and Mahroof 2011). Moreover, honeydew may be more accessible at the higher than lower moisture environment.…”
Section: Discussionmentioning
confidence: 99%